Personalized versus fixed tactile cueing in Parkinson’s disease: Protocol for a randomized controlled trial on gait automaticity - Pablo I. Burgos; William Liu; Carla Silva-Batista; Francesca Baker-Alcalá; Patricia Carlson-Kuhta; Laurie A. King; Fay B. Horak; Kathryn A. Chung; Jodi A. Lapidus; Martina Mancini (PLoS ONE, 2025)
Background Gait automaticity, the ability of the brain to control locomotion with minimal use of executive-attentional resources, is altered in people with Parkinson’s disease (PD). Recently, we showed that step-synchronized tactile cueing improved gait regularity and freezing of gait in PD; however, it is not known if this cueing mode also improves gait automaticity. Thus, this study investigates the effects of step-synchronized tactile cueing (versus fixed cueing) on gait automaticity in the laboratory and during daily life. Methods This is a pilot, randomized, double-blinded study where sixty participants with PD will be randomized into one of two, cueing interventions: 1) personalized, step-synchronized tactile cueing and 2) tactile cueing at fixed intervals. Both cueing interventions use vibrotactile stimulation of wrist bands. During a laboratory study visit, we will measure cortical activity with a wireless, portable functional near-infrared spectroscopy system (fNIRS) during walking tasks. Gait will be assessed using inertial sensors placed on the limbs and trunk. In addition, in daily life, participants will use the same cueing mode at home. The primary outcomes include prefrontal & primary sensory cortex activity. Secondary outcomes are gait stride time, gait local dynamic stability, turn duration and trunk jerk during turning as metrics of gait automaticity in the laboratory. Daily life gait and turning are exploratory measures. Discussion This project will advance the understanding of brain mechanisms associated with walking automaticity during tactile cueing and provide the basis for innovative, personalized cueing to rehabilitate gait automaticity in people with PD. Trial registration ClinicalTrials.gov NCT05818189.